Comparison of three methods used for measurement of radioiodine fixation in thyroid gland of mice - Jeremić Marija Ž. (Nuclear Technology and Radiation Protection, 2013)
The aim of this work is to compare the results of estimation of radioiodine uptake using three methods in a study on mice, and to test reliability of the radioiodine uptake estimation by gamma camera. The study is conducted on 21 white, Swiss-type mice of both sex at age of 10 weeks, weighing between 25 g and 34 g. The mice were injected intraperitoneally with 0.37 ± ± 0.03 MBq of radioiodine 131I. After 72 hours the mice were anesthetized, and radioactivity of thyroid region was measured by gamma camera (the 1st method, in situ). After the measurement, the animals were sacrificed, their thyroid glands were carefully excised together with adjacent trachea and placed at the bottom of a test tube. The radioactivity of the excised tissue was then measured by both gamma camera (the 2nd method) and gamma counter (the 3rd method). This method is treated as a standard and the most accurate. In the study we used Siemens e_cam gamma camera and Wallac Wizard 1470 Automatic Gamma counter. The radioiodine fixation determined using those three methods was 25.25 ± 7.32%, 26.08 ± ± 8.55% and 25.74 ± 7.18%, without statisticaly significant difference s between methods (p > 0.05). The high correlation between the three methods of measuring radioiodine fixation in thyroid gland was observed: (1) the correlation coefficient between the fixation rate obtained by gamma camera in situ and the fixation rate obtained by measuring the radioactivity of extirpated thyroids by gamma camera was 0.869 (p < 0.01); (2) the correlation coefficient between fixation rate obtained by gamma camera in situ and the fixation rate obtained by measuring radioactivity of extirpated thyroids by gamma counter was 0.890 (p < 0.01); (3) the correlation coefficient between fixation rate obtained by measuring radioactivity of extirpated thyroids by gamma camera and the fixation rate obtained by measuring radioactivity of extirpated thyroids by gamma counter was 0.835 (p < 0.01).